2014
DOI: 10.1080/0194262x.2014.914011
|View full text |Cite
|
Sign up to set email alerts
|

Academic Libraries and Outreach to the Sciences: Taking a Closer Look at Research Groups

Abstract: Finding ways to provide support for researchers is of growing concern in academic libraries. In the sciences, research often takes place in a group context, though few studies report specifically on library services targeted to these groups as a whole. Understanding the characteristics and dynamics of research groups can help inform librarians' outreach and service efforts. The purpose of this article is to discuss those strategies that have been successful when approaching research groups, as well as identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…We believe these stages are useful as they provide organisation to the needs of this demographic, that can then be more easily act as a frame of reference for information professionals. Mackenzie (2014) and Gabridge (2009) both concluded that academic librarians are not being capitalised upon in a meaningful way by doctoral students, and while we do not attempt to provide specific advice for instruction and outreach practices, we suggest a consideration of these three stages may be useful for academic librarians to consider in planning their programmes.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…We believe these stages are useful as they provide organisation to the needs of this demographic, that can then be more easily act as a frame of reference for information professionals. Mackenzie (2014) and Gabridge (2009) both concluded that academic librarians are not being capitalised upon in a meaningful way by doctoral students, and while we do not attempt to provide specific advice for instruction and outreach practices, we suggest a consideration of these three stages may be useful for academic librarians to consider in planning their programmes.…”
Section: Resultsmentioning
confidence: 92%
“…Where outreach does exist, it is typically limited to engaging students at all levels and stages and is catered to their specific processes (Reed, 2015). For example, in the medical and scientific disciplines it is common practice to construct research groups that carry out research creation and output as a team (Mackenzie, 2014). There is no such bespoke research strategy for the social science student, which appears to be isolated to undergraduate and graduate students, with no mention of PhD students.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Embedded librarianship is an approach that focusses on "the needs of one or more groups, building relationships within these groups, developing a deep understanding of their work, and providing information services that are highly customized and targeted to their greatest needs" (Shumaker and Talley, 2010). This approach has been leveraged in academic settings, for example, to integrated libraries into research teams (Carlson and Kneale, 2011;MacKenzie, 2014;Corrall, 2014a). Medical librarians have embraced the informationist model of integration into the clinical enterprise (Cooper, 2011;Rankin et al, 2008;Grefsheim et al, 2010).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Rather, the librarian becomes a functional member of the team, and provides information at the time of need rather than waiting for information requests to be presented at a later time. [45][46][47] Engaging with researchers through outreach initiatives to research groups 48 and targeted information literacy instruction to students working in research groups [49][50] are ideas that have received some sparse attention within the literature. However, these previous iterations of outreach to research groups seem not to have considered adopting the longitudinal, team-based approaches utilized by informationists in clinical settings and implementing them within non-clinical research settings.…”
Section: Literature Reviewmentioning
confidence: 99%